Differential Effects of a Glucagon-Like Peptide 1 Receptor Agonist in Non-Alcoholic Fatty Liver Disease and in Response to Hepatectomy. Issue 1 (December 2018) - Valdecantos, M. Pilar; Ruiz, Laura; Pardo, Virginia; Castro-Sanchez, Luis; García-Monzón, Carmelo; Lanzón, Borja; Rupérez, Javier; Barbas, Coral; Naylor, Jaqueline; Trevaskis, James; Grimsby, Joseph; Rondinone, Cristina; et al.
Abstract Non-alcoholic fatty liver disease (NAFLD) is associated with post-operative liver failure (PLF) and impaired liver regeneration. We investigated the effects of a glucagon-like peptide-1 (GLP-1) receptor agonist on NAFLD, PLF and liver regeneration in mice fed chow diet or methionine/choline-deficient diet (MCD) or high fat diet (HFD). Fc-GLP-1 decreased transaminases, reduced intrahepatic triglycerides (TG) and improved MCD-induced liver dysfuction. Macrophage/Kupffer cell-related markers were also reduced although Fc-GLP-1 increased expression of genes related to natural killer (NK), cytotoxic T lymphocytes and hepatic stellate cell (HSC) activation. After partial hepatectomy (PH), survival rates increased in mice receiving Fc-GLP-1 on chow or MCD diet. However, the benefit of Fc-GLP-1 on NASH-like features was attenuated 2 weeks post-PH and liver mass restoration was not improved. At this time-period, markers of NK cells and cytotoxic T lymphocytes were further elevated in Fc-GLP-1 treated mice. Increased HSC related gene expression in livers was observed together with decreased retinyl ester content and increased retinal and retinoic acid, reflecting HSC activation. Similar effects were found in mice fed HFD receiving Fc-GLP-1. Our results shed light on the differential effects of a long-acting GLP-1R agonist in improving NAFLD and PLF, but not enhancing liver regeneration in mice.